The Use of Molecular Markers to Analyze the Genetic Diversity of Indonesian Pepper (Capsicum spp.) Varieties Based on Anthracnose Resistance - Nugroho, Kristianto; Terryana, Rerenstradika T.; Manzila, Ifa; Priyatno, Tri Puji; Lestari, Puji (Makara Journal of Science, 2019)
Anthracnose is an important disease affecting the pepper plant and can lead to significant decreases in harvest yield. In this study, the genetic diversity of Indonesian pepper varieties was analyzed based on anthracnose resistance using molecular markers. DNA collected from 15 pepper varieties belonging to two species—Capsicum annuum L. and C. frutescens L.—was amplified using 14 molecular markers. The fungal isolate Colletotrichum capsici was inoculated into ripe harvested pepper fruits to observe their resistance to anthracnose as indicated by lesion size. Phylogenetic analysis revealed that the 15 pepper varieties could be classified into two major clusters with a genetic similarity coefficient of 0.63, and the pepper varieties exhibited varying degrees of resistance to anthracnose based on lesion size. Using the molecular markers, we were able to differentiate the species of pepper varieties, but not their resistance to anthracnose. All markers used in this study were confirmed to be highly informative (PIC > 0.5), suggesting their potential use in genetic studies on peppers. The marker GPMS29 was found to be significantly associated (P < 0.05) with anthracnose resistance. This information about the genetic diversity of peppers—along with the molecular markers used in our study—could prove to be useful in the further development of breeding programs of pepper plants in terms of anthracnose resistance in Indonesia.